RELATIONS INCLUDED IN THE SUBJECT OF LABOR LAW: THE CURRENT STATE AND THE NEED FOR CHANGES - Vasilyeva, Yu. V.; Drachuk, M. A. (Vestnik Permskogo universiteta. Ûridičeskie nauki (Online), 2024)
Introduction: the paper analyzes relations included in the subject of labor law, their current state, and the need to revise individual provisions of labor legislation. Purpose: to determine the characteristics and the content of relations included in the subject of labor law as well as the correctness of their normative formalization. Methods: scientific analysis, formal-logical, system-structural, comparative-legal, technical-legal methods. Results: the basis of the subject of labor law is comprised of labor relations between the employer and the employee. Since labor is a broad subject area, labor relations require legislative formalization through a set of their most significant features. Judicial practice, relying on domestic and international experience of legal regulation, clarifies the legal characteristics of labor relations by indicating the following aspects: the performance by the employee of a labor function for a fee that is the only and (or) main source of income for him; the integration of the employee into the organizational structure of the employer. While agreeing with this position, the authors provide additional arguments in its support and speak out on the advisability of changing the legal definition of labor relations. Among the relations directly related to labor ones, the following can be distinguished: relations in which the interaction between the parties to the employment contract is mediated by the participation of a third party (control (supervision) bodies, courts, educational organizations, etc.); relations of a collective nature in the world of work. It is proposed to combine relations of a collective nature in the world of work within the frame-work of relations on social partnership. Collective labor disputes (to the extent that the rules for the formation of bodies for their consideration are not related to social partnership) are proposed to be considered as part of relations on resolving labor disputes. The independence of relations regarding material liability of employees seems questionable. In most cases, financial liability of an employee arises on the basis of a disciplinary offense, therefore here relations concerning financial liability lean toward labor relations and relations on resolving labor disputes. Relations regarding the organization of labor and labor management are difficult to clearly define in terms of their content, since in terms of the employer’s implementation of his managerial freedom, such relations do not go beyond the scope of labor relations. According to the authors, this group of legal connections contains the potential for the transition of classical labor law into ‘employment law’. Conclusions: the relations within the subject of labor law are heterogeneous in terms of their significance, parties involved, and features of legal regulation. The need for their normative certainty is mostly determined by the need to protect the weaker party in labor relations – the employee. The dynamics of social relations requires periodic revision of the composition and content of relations that constitute the subject of labor law. Some groups of relations in the subject of labor law partially duplicate each other and therefore they can be united, while other groups require a substantive change or clarification of their denomination in accordance with the actual content of the legal relations.